An intervention to reduce sexual violence on university campus in Ghana: a pilot test of Relationship Tidbits at the University of Cape Coast - Sarah Rominski, PhD; Eugene Darteh, PhD; Michelle Munro-Kramer, PhD (Elsevier, 2017)
Background: Sexual assault is a significant challenge for universities worldwide, affecting the health and academic success of students. Although sexual violence prevention programmes are common at universities in the USA, they are non-existent in Ghana. In this study, we tested an adapted sexual violence prevention programme in students at the University of Cape Coast (UCC), Ghana. Methods: We adapted a sexual violence prevention programme created at the University of Michigan, USA, for use at UCC, Ghana. In February, 2016, we ran focus-group discussions that contributed to the initial adaptation to create a programmed called Relationship Tidbits. In April, 2016, we tested the adapted programme with UCC students. We recruited participants for the beta testing from their halls of residence and via snowball sampling. Students interacted with the programme in small groups of six participants and were encouraged to think aloud and ask questions. Participants completed a pre-programme and post-programme survey that included demographic information and measures of attitudes towards sexual violence and gender equity that had been previously validated for UCC using cognitive interview techniques. These measures are the Illinois Rape Myth Acceptance (IRMA) scale, the Gender Equitable Men (GEM) scale, and the Sexual Relationship Power Scale [SRPS]. We used paired samples t-tests to compare pre-programme and post-programme results. Findings: 71 students-36 men and 35 women with a mean age of 22·9 years (SD 4·7 years)-participated in the programme and testing. Male participants showed improvements in several measures including an increase in the overall mean IRMA scale score (from 60·1 (SD 13·1) to 73·4 (18·3); p<0·0001) as well as the "she asked for it" (p<0·0001), "he didn't mean to" (p=0·004), and "she lied" (p=0·001) subscales. Men also showed an increase in mean GEM score (from 54·5 to 59·5; p=0·011), suggesting more gender equitable attitudes after the training, as well as increases in the violence and reproductive health and disease prevention domains of the GEM (p=0·004 and p=0·021, respectively). Scores for female participants did not change significantly after the programme. Interpretation: Our preliminary findings suggest that the adapted programme for university students could change attitudes that are known to be associated with the perpetration of sexual violence. Because rape myth acceptance is common in this setting, the reduction in rape myth acceptance in men is important. Future work will include a more rigorous evaluation of the outcomes of this programme with respect to sexual violence attitudes and behaviours. Funding: None.